2015
DOI: 10.1557/opl.2015.154
|View full text |Cite
|
Sign up to set email alerts
|

Research Experiences for Students: Interdisciplinary skill development to prepare the future workforce for success

Abstract: Research Experiences for Undergraduates (REU) programs traditionally function as a recruitment vehicle to encourage students to pursue further studies in STEM (Science, Technology, Engineering and Math) and as an opportunity for STEM majors to delve deeper into their chosen fields of study. Based on a critical examination of REU student feedback, evaluators at CRISP (Center for Research on Interface Structures and Phenomena) have found that in addition to these conventional benefits of research-based experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…According to study of V M Bazurin et.al, it was found that the system of interdisciplinary practice-oriented problems of mathematical content was more effective than that of problems given in school textbooks [5] . Besides, other educators have studied the application of interdisciplinary teaching in the junior and senior high school [6] . However, there was a limited number of studies investigating the performance of higher vocational college students after accepting interdisciplinary teaching.…”
Section: Introductionmentioning
confidence: 99%
“…According to study of V M Bazurin et.al, it was found that the system of interdisciplinary practice-oriented problems of mathematical content was more effective than that of problems given in school textbooks [5] . Besides, other educators have studied the application of interdisciplinary teaching in the junior and senior high school [6] . However, there was a limited number of studies investigating the performance of higher vocational college students after accepting interdisciplinary teaching.…”
Section: Introductionmentioning
confidence: 99%